1980
DOI: 10.1093/jn/110.5.916
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vitamin E on the Mitogenic Response of Murine Lymphoid Cells

Abstract: The effect of vitamin E on mitogenesis by polyclonal activators was studied and the vitamin was found to be stimulatory but selective in its action. Vitamin E itself is a mitogen for murine spleen cells. At suboptimal vitamin concentrations, it was capable of stimulating the response to low levels of the thymus-dependent lymphocyte (T cell) mitogen, concanavalin A (conA), but not when conA was itself at optimal levels. When vitamin E was added to the diet at normal levels, it was not as effective in stimulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…Weight of draining auricular lymph nodes, lymph node cell number in the lymph nodes and 3HTdR incorporation into the cells of control mice fed a vitamin E-adequate diet were higher than those of the control mice fed a vitamin E-deficient diet (Table 1 , control). Lymph node weight, lymph node cell number and 3HTdR incorporation were increased by topical exposure to DNCB, and these values from mice fed a vitamin E-adequate diet were greater than those from mice fed a vitamin E-deficient diet ( of lymphocytes to mitogen (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, to our knowledge, this is the first demonstration of the effect of vitamin E on sensitization response to contact allergens.…”
Section: Discussionmentioning
confidence: 98%
“…Weight of draining auricular lymph nodes, lymph node cell number in the lymph nodes and 3HTdR incorporation into the cells of control mice fed a vitamin E-adequate diet were higher than those of the control mice fed a vitamin E-deficient diet (Table 1 , control). Lymph node weight, lymph node cell number and 3HTdR incorporation were increased by topical exposure to DNCB, and these values from mice fed a vitamin E-adequate diet were greater than those from mice fed a vitamin E-deficient diet ( of lymphocytes to mitogen (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, to our knowledge, this is the first demonstration of the effect of vitamin E on sensitization response to contact allergens.…”
Section: Discussionmentioning
confidence: 98%
“…Vitamin E has also been shown to cause an erythropoietic response in anemic patients (10,28) and to restore cellmediated immunity by increasing the T-cell number (8).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E is known to enhance immune responses, and to stimulate mitogenic responses of lymphocytes. [3][4][5][6] The increased IgE levels caused by vitamin E-deficiency in type I allergy responses with DNCB-sensitization may be derived from increased Th2 cell activation and the production of IL-4.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E enhances immune responses, and stimulates mitogenic responses of lymphocytes and antibody production. [3][4][5][6] Our previous studies have shown that vitamin E-deficiency in mice brings about decreased contact sensitization responses to 2,4-dinitrochlorobenzene (DNCB). 7) On the other hand, nitrogen dioxide (NO 2 ) is a free radical toxin usually present in polluted urban and room air (0.02-0.2 ppm), and in fresh smoke or cigarrette smoke (upto 100 ppm).…”
Section: Introductionmentioning
confidence: 99%